HCV eradication does not impact gut dysbiosis or systemic inflammation in cirrhotic patients. Issue 6 (15th July 2016) - Bajaj, J. S.; Sterling, R. K.; Betrapally, N. S.; Nixon, D. E.; Fuchs, M.; Daita, K.; Heuman, D. M.; Sikaroodi, M.; Hylemon, P. B.; White, M. B.; Ganapathy, D.; Gillevet, P. M.
Summary: Background: Eradication of hepatitis C virus (HCV) is increasing but its residual impact on the pro‐inflammatory milieu in cirrhosis, which is associated with gut dysbiosis, is unclear. Aim: To define the impact of sustained virological response (SVR) on gut dysbiosis and systemic inflammation in HCV cirrhosis patients. Methods: Cirrhotic out‐patients with HCV with/without SVR (achieved >1 year prior) and age‐matched healthy controls underwent serum and stool collection. Serum was analysed for IL‐6, TNF‐α and endotoxin while stool microbiota analysis was performed using multitagged pyrosequencing. Microbial comparisons were made using UNIFRAC and cirrhosis dysbiosis ratio (lower score indicates dysbiosis). Comparisons were performed between cirrhotics with/without SVR and controls vs. cirrhotic patients. Results: A total of 105 HCV cirrhotics and 45 age‐matched healthy controls were enrolled. Twenty‐one patients had achieved SVR using pegylated interferon + ribavrin a median of 15 months prior. No significant differences on demographics, cirrhosis severity, concomitant medications or diabetes were seen between cirrhotics with/without SVR. There was no significant difference in overall microbiota composition (UNIFRAC P = 0.3) overall or within specific microbial families (cirrhosis dysbiosis ratio median 1.3 vs. 1.0, P = 0.45) between groups with/without SVR. This also extended towards IL‐6, TNF‐α and endotoxin levels. Both cirrhosis groups, however, had significant dysbiosis compared to healthy controls [UNIFRAC P = 0.01, cirrhosis dysbiosis ratio (1.1 vs. 2.9, P < 0.001)] along with higher levels of endotoxin, IL‐6 and TNF‐α. Conclusions: Gut dysbiosis and a pro‐inflammatory systemic milieu, are found in HCV cirrhosis regardless of SVR. This persistent dysbiosis could contribute towards varying rates of improvement after HCV eradication in cirrhosis.